Enriquecimiento en manool a partir de biomasa de Enterolobium cyclocarpum (Jacq.) Griseb. - Calderón Ordaz, Ana Karen (Universidad Michoacana de San Nicolás de Hidalgo, 2022)
Manool is a molecule of interest due to its pharmacological and biotechnological properties. Manool is obtained by chemical or biochemical synthesis and extraction from biological materials. In plants, this molecule is found with its derivatives and its enrichment is a difficult process. Therefore, this work proposes a methodology to obtain manool-enriched fractions from the heartwood residue of Enterolobium cyclocarpum (Jacq.) Griseb. (Parota) through a series of processes and unit operations. The extractable compounds of E. cyclocarpum (21.46 ± 0.02%) were obtained by successive extraction in ascending polarity with a Soxhlet equipment. Characteristic manool signals were detected in the acetone extracts (7.50 ± 1.82%) by 1H NMR. The Soxhlet extraction parameters were determined by a 23-factorial design (p ≤ 0.05) where the extraction time, the mass/volume ratio, and the temperature were evaluated as control variables on the extract yield. The time (3 h) and the mass/volume ratio (1/30 g/mL) had a significant effect on the yield of the extracts. The acetone extracts were diluted in hexane. The manool in solution was filtered off and enriched by column chromatography. Compound B (20 mg) was identified as manool by 1H NMR, IR and GC/MS. Manool was obtained from E. cyclocarpum heartwood from three different regions. The technical-economic analysis showed that the manool enrichment process from E. cyclocarpum biomass for a production scale of 10 kg/d is profitable and feasible as a sustainable process.

El manool es una molécula de interés por sus propiedades farmacológicas y biotecnológicas. El manool se obtiene por síntesis química, bioquímica o de material biológico. En plantas, esta molécula se encuentra junto con sus derivados y su enriquecimiento es un proceso difícil. Por ello, la propuesta es obtener fracciones enriquecidas en manool a partir del residuo de duramen del Enterolobium cyclocarpum (Jacq.) Griseb. (Parota) mediante un conjunto de procesos y operaciones unitarias. Los compuestos extraíbles totales del E. cyclocarpum (21.46 ± 0.02%) se obtuvieron por extracción sucesiva en polaridad ascendente con un equipo Soxhlet. Señales características de manool se detectaron en los extractos acetónicos (7.50 ± 1.82%) por 1H-RMN. Los parámetros de extracción en Soxhlet se determinaron por un diseño factorial 23 (p ≤ 0.05) donde se evaluó el tiempo de extracción, la relación masa/volumen y la temperatura, como variables control sobre el rendimiento del extracto. El tiempo (3 h) y la relación masa/volumen (1/30 g/mL) tuvieron un efecto significativo en el rendimiento de los extractos. Los extractos acetónicos se diluyeron en hexano. El manool en disolución se separó por filtración y se enriqueció por cromatografía en columna. El compuesto B (20 mg) se identificó como manool por 1H-RMN, IR y CG/MS. El manool se obtuvo a partir de biomasa de duramen de E. cyclocarpum de tres regiones distintas. El análisis técnico-económico mostró que el proceso de enriquecimiento en manool a partir de biomasa de E. cyclocarpum para una escala de producción de 10 kg/d es rentable y factible como un proceso sustentable.
Facultad de Ingeniería Química. Maestría en Ciencias en Ingeniería Química
Keywords: info:eu-repo/classification/cti/7; FIQ-M-2022-0533; Extracción sólido-líquido; Compuestos extraíbles; Duramen; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/6761